Drug transporters in breast cancer: response to anthracyclines and taxanes. Issue 9 (September 2015) - Kümler, Iben; Stenvang, Jan; Moreira, José; Brünner, Nils; Nielsen, Dorte Lisbet
<x xml:space="preserve">Abstract</x> Despite the advances that have taken place in the past decade, including the development of novel molecular targeted agents, cytotoxic chemotherapy remains the mainstay of cancer treatment. In breast cancer, anthracyclines and taxanes are the two main chemotherapeutic options used on a routine basis. Although effective, their usefulness is limited by the inevitable development of resistance, a lack of response to drug-induced cancer cell death. A large body of research has resulted in the characterization of a plethora of mechanisms involved in resistance; ATP-binding cassette transporter proteins, through their function in xenobiotic clearance, play an important role in resistance. We review here the current evidence for drug transporters as biomarkers and the benefit of adding drug transporter modulators to conventional chemotherapy.